Techniques to Obtain Good Resolution and Concentrated Time-Frequency Distributions: A Review. (9th June 2009) - Shafi Shafi, Imran Imran; Ahmad Ahmad, Jamil Jamil; Shah Shah, Syed Ismail Syed Ismail; Kashif Kashif, F. M. F. M.
Abstract : We present a review of the diversity of concepts and motivations for improving the concentration and resolution of time-frequency distributions (TFDs) along the individual components of the multi-component signals. The central idea has been to obtain a distribution that represents the signal's energy concentration simultaneously in time and frequency without blur and crosscomponents so that closely spaced components can be easily distinguished. The objective is the precise description of spectral content of a signal with respect to time, so that first, necessary mathematical and physical principles may be developed, and second, accurate understanding of a time-varying spectrum may become possible. The fundamentals in this area of research have been found developing steadily, with significant advances in the recent past.